2016
DOI: 10.28945/3568
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Computerized Gloss Presentation Format on Reading Comprehension: A Cognitive Load Perspective

Abstract: In recent years, gloss presentation format or the location where a gloss appears with respect to its related target word has received renewed attention. Research suggested that different gloss presentation formats could have differential effects on reading comprehension and/or vocabulary learning. This study hypothesized that the effectiveness of different computerized gloss presentation formats in reading comprehension could be explained by drawing on the split-attention effect within the framework of cogniti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
3
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 62 publications
1
3
0
Order By: Relevance
“…Elekaei et al's (2015) four-group study compared the efficacy of glosses as footnotes, glosses in margins, glossaries, and interlinear glosses among English learners to find that interlinear glossing led to higher rates of reading comprehension than did all other gloss locations. These results, like AbuSeileek (2008) and Marefat et al (2016), seem to suggest that when it comes to gloss location, proximity may play a role in glossing efficacy. The mean values for reading comprehension results in Elekaei et al's (2015) study were, in descending order: interlinear, margins, footnotes, and a separate glossary.…”
Section: B Studies Of Gloss Locationsupporting
confidence: 52%
“…Elekaei et al's (2015) four-group study compared the efficacy of glosses as footnotes, glosses in margins, glossaries, and interlinear glosses among English learners to find that interlinear glossing led to higher rates of reading comprehension than did all other gloss locations. These results, like AbuSeileek (2008) and Marefat et al (2016), seem to suggest that when it comes to gloss location, proximity may play a role in glossing efficacy. The mean values for reading comprehension results in Elekaei et al's (2015) study were, in descending order: interlinear, margins, footnotes, and a separate glossary.…”
Section: B Studies Of Gloss Locationsupporting
confidence: 52%
“…This might be why participants who benefitted from feedback on sentence‐integrations remained stable in their global text comprehension (see Figure 7), whereas participants who received feedback on vocabulary always decreased (see Figure 5). Aligned with this, information which was intended to support foreign‐language text processing in adults had a better effect when it was presented in an integrated than separated form (AbuSeileek, 2011; Marefat et al, 2016).…”
Section: Discussionmentioning
confidence: 99%
“…Both studies suggested that when presenting learning materials, the split-attention effect should be considered along with task nature and L2 proficiency. In another study, Marefat et al (2016) compared the effects of in-text and marginal glosses on preintermediate learners’ L2 English reading comprehension. For in-text glosses, first language (L1) glosses popped up near a L2 word after it was clicked (integrated format), whereas for marginal glosses, L1 glosses appeared at the right margin (separated format).…”
Section: Presentation Formats In L2 Learningmentioning
confidence: 99%
“…Learner perceptions can be investigated both quantitatively and qualitatively (Wesely, 2012). Among the eight L2 studies on presentation formats reviewed above, only four recorded learner perceptions by collecting quantitative difficulty ratings for learning with different formats and/or for completing posttreatment tests (Lee & Kalyuga, 2011; Marefat et al, 2016; Yeung, 1999; Yeung et al, 1997). Notably, these difficulty ratings were mainly used to calculate instructional efficiency scores to compare the efficacy of different formats (see Paas et al, 2003) rather than to provide detailed analysis of learner perceptions.…”
Section: Learner Perceptions and Instructional Practicementioning
confidence: 99%